Al-Ikhsan / Mohamad Azrel Amer Mohd Azman - Mohd Azman, Muhammad Azrel Amer (2021)
Al-Ikhsan is a local Malaysian company that is still managing to compete with international names. Al-Ikhsan Sports is the number one multi-brand, multi-category sports retailer in Malaysia, with 128 stores, and that number expected to grow to 140 by the end of this year. The company was founded by an enterprising first-generation entrepreneur when he was just in his early twenties, Mr Ali Hassan bin Mohammed Hassan. The founder saw the local population’s need for sports brands like Nike and Adidas and decided to start with a 150 square foot shop at a small shopping mall in the city of Johor Bahru. From a singular concept of Al-Ikhsan Sports, we now have four clearly differentiated concepts built around the same core philosophy which will allow us to seamlessly straddle different consumer segments without any conflict or confusion. We focus on curating our brands in line with the consumers’ expectations,” explains Vach Pillutla, CEO of Al-Ikhsan Sports. “To me, business, like war, is won on the basis of a clear strategy and positioning and it is always better to go into that war with multiple weapons in your arsenal.